ANALYSIS OF COMPETITION INDUSTRIAL ENTERPRISES - A. O. Egorova; N. K. Zokirova (Вестник Мининского университета, 2017)
The paper analyzed and systematized the definition of "competition" proposed by domestic and foreign scholars in the field of strategic management, based on these discovered and refined essence of the concept of "competition". We consider the price and non-price competition. Examples are given of the methods of competition used in the practice of industrial activities. Substantiated that the forms and methods of competition must be constantly improved through the search for new competitive advantages.